Feasibility and repeatability of ocular biometry measured with Lenstar LS 900 in a large group of children and adolescents. (27th March 2021) - Rauscher, Franziska G; Hiemisch, Andreas; Kiess, Wieland; Michael, Ralph
Abstract: Purpose: To evaluate the feasibility and repeatability of Lenstar LS 900 biometry measurements in a paediatric population. Methods: Children were examined as part of the LIFE Child Study (Leipzig Research Centre for Civilization Diseases), a population‐based study in Leipzig, Germany. Altogether, 1917 children, aged from 3.5 to 17.5 years, were assessed with the Haag Streit Lenstar LS 900. Three consecutive measurements of the right eye were analysed for axial length, central corneal thickness, anterior chamber depth, aqueous depth, lens thickness and flat and steep corneal radii. The number of successful measurements and repeatability were evaluated for each parameter and three age bands (3.5 to 6.5 years, 6.5 to 10.5 years and 10.5 to 17.5 years). Results: Best measurement feasibility was found for axial length and central corneal thickness (91% to 100%), followed by flat and steep corneal radii (86% to 100%), anterior chamber and aqueous depth (76% to 92%) and lens thickness (50% to 81%), with higher numbers for older children. Repeatability values (in mm) were: axial length 0.025 to 0.035; central corneal thickness 0.003 to 0.027; aqueous depth 0.024 to 0.058; anterior chamber 0.024 to 0.054; lens thickness 0.034 to 0.067. An overall trend showed better repeatability for older children, especially for central corneal thickness, aqueous depth and lens thickness. Conclusions: For ocular biometry in the paediatric population, axial length, central corneal thickness, flat and steep corneal radii can be measured very reliably even in children from 4 years old onward using the Lenstar LS 900. Lens thickness can be quantified in a limited number of younger children. Repeatability was high for all variables investigated. Repeatability improved with age, reaching adult values in the adolescent age band. Established repeatability limits can be applied in future studies as a quality parameter.